2020
DOI: 10.1177/1557988320937124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Negative Life Events and Social Support on Nonsuicidal Self-Injury Among Chinese Middle School Students

Abstract: The field of nonsuicidal self-injury (NSSI) is dominated by research conducted with Caucasian majority samples in Western countries such as North America and Europe. Far less NSSI-related research is conducted in non-Western cultures, even though NSSI behavior is a growing issue in China where studies have found that NSSI among youth occurs at a higher prevalence and has an earlier onset as compared to Western studies. Based on the data collected from middle school students in Xi’an, China, this article tries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 17 publications
(22 reference statements)
2
38
0
4
Order By: Relevance
“…The findings supported our hypothesis that adolescents who experienced stressful life events are more likely to engage in NSSI. This result confirmed the findings from previous studies that showed a significant positive correlation between stressful life events and adolescent NSSI ( 16 18 , 44 ). This result also is consistent with what would be expected based on the general strain theory ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings supported our hypothesis that adolescents who experienced stressful life events are more likely to engage in NSSI. This result confirmed the findings from previous studies that showed a significant positive correlation between stressful life events and adolescent NSSI ( 16 18 , 44 ). This result also is consistent with what would be expected based on the general strain theory ( 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous research showed that stressful life events are strongly correlated with adolescents' risky behaviors (13,14), consistent with general strain theory (15). In line with this theory, stressful life events have been shown to be associated with adolescent NSSI in correlational studies (16)(17)(18) and longitudinal studies (19-21). For example, in a longitudinal study, Baetens et al (19) found that adolescents' stressful life events were significantly positively associated with NSSI 18 months later.…”
Section: Stressful Life Events and Adolescent Nssimentioning
confidence: 73%
“…Research shows that up to 79% of self-injurers have experienced child abuse or bullying [ 5 ]. Most theoretical models also consider that early adverse experiences and negative sexual events have an important impact on R-NSSI behavior among adolescents [ 6 , 7 , 8 ]. International studies show that 20% to 30% of students have been subjected to verbal and visual violence, with verbal violence being a common factor in all kinds of NSSI, leading them to become both victims and perpetrators [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, since a collectivistic culture is predominant in China, interpersonal connectedness is highly valued [ 23 ] and the interpersonal model [ 24 ] may be a particularly relevant framework for understanding NSSI development among Chinese adolescents. Previous studies conducted among Chinese adolescents have found that interpersonal factors such as peer victimization [ 25 ], negative life events, and less social support [ 26 ] are relevant risk factors for NSSI. On the other hand, the Chinese Confucian culture emphasizes individuals’ positive attitude when facing adversity [ 27 ].…”
Section: Introductionmentioning
confidence: 99%